2017
DOI: 10.1007/s11524-017-0188-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-injection Drug Use and Injection Initiation Assistance among People Who Inject Drugs in Tijuana, Mexico

Abstract: Although most people who inject drugs (PWID) report receiving assistance during injection initiation events, little research has focused on risk factors among PWID for providing injection initiation assistance. We therefore sought to determine the influence of non-injection drug use among PWID on their risk to initiate others. We used generalized estimating equation (GEE) models on longitudinal data among a prospective cohort of PWID in Tijuana, Mexico (Proyecto El Cuete IV), while controlling for potential co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 55 publications
2
36
2
Order By: Relevance
“…Finally, we found that measures of higher drug use activity—such as injection frequency and polydrug IDU—were significantly associated with an increased risk that study participants reported providing injection initiation assistance. This adds to a small but growing evidence base identifying these as risk factors for the provision of injection initiation assistance among PWID (Bluthenthal et al, 2015b; Hamida et al, 2017; Rafful et al, 2017). Given that methamphetamine IDU was a strong predictor of initiating others, future OAT-based intervention research should also examine polydrug use to address the role of opioid use in driving PWID’s increased risk for initiating others.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Finally, we found that measures of higher drug use activity—such as injection frequency and polydrug IDU—were significantly associated with an increased risk that study participants reported providing injection initiation assistance. This adds to a small but growing evidence base identifying these as risk factors for the provision of injection initiation assistance among PWID (Bluthenthal et al, 2015b; Hamida et al, 2017; Rafful et al, 2017). Given that methamphetamine IDU was a strong predictor of initiating others, future OAT-based intervention research should also examine polydrug use to address the role of opioid use in driving PWID’s increased risk for initiating others.…”
Section: Discussionmentioning
confidence: 96%
“…The primary outcome was defined as recently assisting others in their first injection (confirmed via endorsement of the following survey item: “In the past 6 months, have you helped someone inject who had never injected before?”). The independent variable of interest was active OAT enrollment, defined via endorsement of the statement: “In the past 6 months have you been in (methadone/methadose program or Suboxone) treatment?” Covariates were selected based on previous literature and included: cohort, age, gender, race/ethnicity, marital status, homelessness status, current neighborhood of residence, any non-injection drug use, recent IDU frequency (defined as daily vs. less than daily vs. none), recent public injection, recent cocaine IDU, recent methamphetamine IDU, recent heroin IDU, recent speedball (i.e., heroin and cocaine in combination) IDU, recent prescription opioid IDU, and type of OAT (Bluthenthal et al, 2015b; Fuller et al, 2005; Hamida et al, 2017; Ickowicz et al, 2017). The categories for current neighborhood of residence (i.e., Downtown Eastside [DTES], Downtown South [DTS], vs Other) were chosen based on data showing distinct high-risk drug practices in these two areas.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, although it is possible to learn to inject oneself without the help of PWID, this is difficult and rare (Crofts et al, 1996; Doherty et al, 2000; Day et al, 2005; Kermode et al, 2007; Rotondi et al, 2014). Among samples of experienced injectors, the proportion who have ever helped with first injections has ranged from 14 percent (Hamida et al, 2018) to 47 percent (Bluthenthal et al, 2014; Crofts et al, 1996; Day et al, 2005; Hunt et al, 1998; Rhodes et al, 2011), although in one study this rate was 69 percent (Kermode et al, 2007). These data suggest that a minority of PWIDs help with others’ first injection, yet account for the great majority of incident injection drug use episodes.…”
Section: Introductionmentioning
confidence: 90%
“…Initiation into IDU from the perspective of the initiate has been well studied (Werb et al, 2013; Guise et al, 2017), but data are more limited on the predictors and perspectives of experienced PWID assisting novices with their first injections. Studies of those who help with first injections have shown that assisting is associated with various demographic factors (Crofts et al, 1996; Hamida et al, 2018; Kermode et al, 2007; Rotondi et al, 2014), a range of drug-use patterns and injection promoting behaviors (e.g., talking positively about injection to novices, injecting in front of persons who do not inject drugs (non-PWID)) (Bluthenthal et al, 2014; Bryant and Treloar 2008; Crofts et al, 1996; Day et al, 2005; Hamida et al, 2018; Kermode et al, 2007; Rotondi et al, 2014), and other factors (Bluthenthal et al, 2014; Bryant and Treloar, 2008). Few variables have emerged from more than one study as significant predictors of assisting, in part because of limited overlap in the predictors examined.…”
Section: Introductionmentioning
confidence: 99%